Konsumsi Ekstrak Daun Kelor Dalam Meningkatkan Kadar Hemoglobin Pada Ibu Hamil - Tri Hartati; Sunarsih Sunarsih (Malahayati Nursing Journal, 2021)
ABSTRACT: CONSUMING OF MORINGA LEAF EXTRACT IN INCREASING HEMOGLOBIN LEVEL TOWARD PREGNANT WOMAN. Introduction:Anemia rate on pregnancy in Indonesia showed quite high level that  was 3,8% on the first trimester, 13,6% on second trimester and 24,8% on the third trimester. Most of anemia whom suffered was lack of zinc which can be resolved through giving nutrition regularly and nutritive enhancement. Purpose:The purpose of this research was in knowing the influence in consuming of moringa leaf extract through increasing hemoglobin level toward pregnant woman. Method:This was a quantitative with Quasi Experimental research design and one group pretest- posttest design approach. Population in this research was pregnant woman on third semester. The amount of sample was 33 people whom gotten by using Purposive sampling technique. This research was done in M.Mataram Public Health Center, West Lampung regency,on February-August 2018. Data collecting used observation sheet and Hemoglobin Test. Bivariate data analysis used T-Test. Result: An average of hemoglobin level the third trimester pregnant woman before given Moringa Leaf extracts with mean 9.642 and deviation standard 0. 6103. After consuming Moringa Leaf extracts was gotten an average hemoglobin level pregnant woman, 10.648 and deviation standard, 0.9582.  The result of statistic test was gotten Value p- Value 0,000 0,005Conclusion: There was influence in consuming Moringa Leaf extracts toward enhancement of hemoglobin level on pregnant woman. Then for midwife gives counseling to pregnant woman regularly about the importance of consuming meal which is rich Fe content and Vitamin C such as moringa leaf. Key Words: Moringa Leaf, Hemoglobin Level, Pregnant Woman INTISARI: KONSUMSI EKSTRAK DAUN KELOR DALAM MENINGKATKAN KADAR HB PADA IBU HAMIL Latar Belakang: Angka kejadian anemia pada kehamilan di Indonesia menunjukkan nilai yang cukup tinggi yaitu 3,8% pada trimester I, 13,6% pada trimester II dan 24,8% pada trimester III. Kebanyakan anemia yang diderita adalah kekurangan zat besi yang dapat diatasi melalui pemberian zat gizi secara teratur dan peningkatan gizi.Tujuan: Tujuan penelitian untuk mengetahui pengaruh konsumsi  ekstrak daun kelor dengan meningkatkan kadar Hb pada ibu hamil.Metode Penelitian: Jenis penelitian ini adalah kuantitatif dengan desain penelitian Quasi Eksperimental dan pendekatan one group pretes-postes design. Populasi dalam penelitian adalah ibu hamil trimester III. Sampel berjumlah 33 orang yang didapatkan dengan menggunakan teknik Purposive  sampling. Penelitian telah dilakukan di Puskesmas M. Mataram Kab. Lampung Selatan pada Februari – Agustus 2018.  Pengumpulan data menggunakan lembar observasi dan HB Test. Analisa data bivariate  menggunakan uji t-test. Hasil: Rata-rata kadar Hemoglobin ibu hamil trimester III sebelum diberikan ekstrak daun kelor dengan Mean 9.642 dan Standar Deviasi 0.6103. Sesudah mengkonsumsi ekstrak daun kelor didapatkan rata – rata kadar HB ibu hamil sebesar 10.648 dan Standar Deviasi 0.9582. Hasil uji statistic didapatkan nilai p- value 0,000 0,005Kesimpulan: ada pengaruh konsumsi ekstrak daun kelor terhadap peningkatan kadar hemoglobin ibu hamil. Kepada bidan agar rutin memberikan penyuluhan kepada ibu hamil, tentang pentingnya mengkonsumsi makanan  yang kayak kandungan Fe dan Vitamin C seperti daun kelor. Kata Kunci     :Daun Kelor, Kadar Hb,Ibu Hamil